2012
DOI: 10.1038/cgt.2012.62
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of HER2 retargeted herpes simplex virus as therapy for high-grade glioma in immunocompetent mice

Abstract: Replication-competent oncolytic herpes simplex viruses (HSVs) are considered a promising therapeutic approach for treatment of high-grade gliomas (HGGs), which are usually resistant to all the available treatments. We previously demonstrated that R-LM113, a recombinant HSV-1 fully retargeted to the human epidermal growth factor receptor 2 (HER2), is safe and prolongs survival of immunodeficient NOD/SCID mice in an intracranial model of HGG. However, because the treatment is designed to be employed on immunocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…Repeated injections of R-LM249 doses higher than 10 6 pfu left 60% of mice tumor-free, and dramatically reduced the tumor size in the remaining 40%. Recently, a HSV retargeted to HER-2 showed efficient antitumor activity in an intracranial model of high-grade glioma in immunosuppressed and immunocompetent mice [7], [9]. Overall, these findings demonstrated that R-LM249 is effective in killing HER-2+ tumors in vivo, when administered locally [6].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Repeated injections of R-LM249 doses higher than 10 6 pfu left 60% of mice tumor-free, and dramatically reduced the tumor size in the remaining 40%. Recently, a HSV retargeted to HER-2 showed efficient antitumor activity in an intracranial model of high-grade glioma in immunosuppressed and immunocompetent mice [7], [9]. Overall, these findings demonstrated that R-LM249 is effective in killing HER-2+ tumors in vivo, when administered locally [6].…”
Section: Introductionmentioning
confidence: 88%
“…The strategy pursued in our laboratories is to modify HSV-1 tropism, and efficiently retarget the virus to cancer-associated cell-surface molecules, such as the human epithelial growth factor receptor 2 (HER-2), a member of the tyrosine kinase receptors [4][9]. The clinical impact of the HER-2 oncogene stems from the fact that it is overexpressed in human breast and ovary carcinomas (>200,000 new cancer cases each year in the U.S.), and correlates with worsened prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The deleted portions of gD were amino acids (aa) 6 to 38 in the recombinant HSV construct named R-LM113 and the entire gD core (aa 61 to 218) in the recombinant HSV construct named R-LM249 (14, 15). In preclinical studies, R-LM113 and R-LM249 exerted antitumor activities against HER2-positive breast and ovarian cancers and against glioblastoma (14, 16, 2123). Recently, we showed that not only gD but also gH can be a retargeting tool.…”
Section: Introductionmentioning
confidence: 99%
“…The Campadelli-Fiume group has employed recombinant oHSV containing an anti-HER2 scFv in gD to target HER2-expressing tumor cells [7,5560] in culture and in vivo . Early studies employed gD recombinants that could still enter cells by binding to the canonical gD receptor nectin-1 [5557,60] and although they displayed good efficacies in ovarian and glioma tumor models in mice [55,57,60], exclusive targeting of the HER2 tumor receptor was not achieved. Subsequent reports from this group [7,58,59] employed oHSV that were mutationally inactivated for binding to nectin-1 and HVEM, resulting in sole entry into HER2-bearing tumor cells.…”
Section: Retargeting Of Hsv Attachment/entrymentioning
confidence: 99%